Understanding the relapse process: exploring Iranian women's substance use experiences - Maryam Khazaee-Pool; Tahereh Pashaei; Roghayeh Nouri; Parvaneh Taymoori; Koen Ponnet (BMC, 2019)
Abstract Background Relapse is one of the main challenges that must be tackled in the drug addiction treatment. Different factors contribute to the relapse process but it remains unclear how relapse occursin women. Describing the relapse phenomenon in women might be of interest to practitioners and academics. The aim of this study was to explore the relapse experiences of Iranian women with a substance use disorder. Methods Qualitative in-depth interviews were conducted with women with a substance use disorder. The interviews contained open-ended questions regarding relapse experiences during previous treatment. Interviews were digitally recorded. Data were analyzed using the content analysis method. Results In total, 20 women who use drugs took part in the study. The mean age of the women was 34.57 (age range = 9.6 years), and the minimum age of participants was 23 years. The following five main themes were explored: socioeconomic backgrounds, physical complications of drug withdrawal, psychological burden of drug withdrawal, family atmosphere, and cultural factors. The findings highlighted the different treatment needs in women with a substance use disorder. Conclusions Based on the interviews, it seems necessary to develop female-specific comprehensive treatment programs by putting more emphasis on pain treatment intervention, relapse prevention, the diagnosis and treatment of mental disorders, couples counseling, and financial support. Furthermore, policymakers should be committed to providing a nonjudgmental social environment to remove or reduce stigma of women with drug use problems.